Melt Fusion Techniques for Solubility Enhancement: A Comparison of Hot Melt Extrusion and KinetiSol® Technologies - Srinivas Ajjarapu; Srikanth Banda; Pratap Basim; Narendar Dudhipala (MDPI AG, 2022)
A successful candidate for oral drug delivery needs to possess adequate solubility and dissolution rate to elicit its therapeutic action. Extensive research is being carried out to enhance the solubility of poorly soluble drugs through a number of techniques involving polymeric and non-polymeric approaches. Non-polymeric approaches such as micronization and nanocrystals are successful in improving the apparent solubility of drugs, but the sustenance of solubility is not always possible. Amorphous solid dispersions (ASDs) lead to solubility enhancement as well as the maintenance of solubility with the assistance of polymers, thereby improving bioavailability. Spray drying, hot melt extrusion (HME), and KinetiSol® technologies are some of the techniques capable of manufacturing ASDs. Each of these techniques has its own advantages and disadvantages in terms of processing challenges and applicability in preparing ASDs. The latter two technologies are similar in being fusion and non-solvent techniques to improve solubility. This review compares both HME and KinetiSol® techniques regarding mechanism, equipment design, formulation, and process parameters involved and scalability.